Severe pediatric asthma therapy: Omalizumab—A systematic review and meta-analysis of efficacy and safety profile - Fenu, Grazia; La Tessa, Andrea; Calogero, Claudia; Lombardi, Enrico (Frontiers in Pediatrics, 2023)
Background: Omalizumab is the first biological therapy that has been used in moderate-severe asthma and certainly the one with the highest number of publications. Methods: A systematic review and meta-analysis was performed to examine two critical outcomes of omalizumab therapy, asthma exacerbation rate and the reduction of use of inhaled corticosteroids (ICS), and the improvement of the lung function as secondary outcome, using the following keywords in the MEDLINE database: “anti-IgE; severe asthma; children; randomized controlled trial”. We specifically selected papers that included patients with moderate to severe asthma and collected data on children and adolescents. Results: A total of 4 RCT studies (total number of patients=1239) were included in the analysis. The reported data on exacerbations, showed an overall improvement in exacerbation rate with a decrease use of inhaled steroids and some other minimal clinically important difference (MCID). Conclusions: Our systematic review confirms the known findings that omalizumab therapy decreases asthma exacerbation rate and reduces background therapy inhaled steroid dose. Therefore, add-on therapy with omalizumab shows a good efficacy and safety profile, thus proving to be a useful additional therapeutic option.